Salvia guidongensis sp. nov.: unraveling a critical evolutionary link in East Asian Salvia from Central China integrating morphology, phylogeny, and plastid genomics - Huang, Yan-Bo; Qi, Zhe-Chen; Feng, Jie-Ying; Ge, Bin-Jie; Huang, Cun-Zhong; Feng, Yu-Qing; Wu, Jing; Wei, Pu-Rui; Ito, Takuro; Kokubugata, Goro; Li, Pan; Wei, Yu-Kun (Frontiers in Plant Science, 2024)
Introduction Salvia L., representing the largest genus within the mint family, is noted for its global distribution of approximately 1000 species, with East Asia, and particularly China, recognized as a critical center of diversity for the genus. Methods Our research was conducted through extensive fieldwork in Guidong County, Hunan Province, China, where we identified a previously undescribed species of Salvia. The identification process involved detailed morphological observations, phylogenetic analyses, and plastid genomics. Results The newly discovered species, Salvia guidongensis, exhibits unique characteristics not commonly observed in the East Asian lineage of Salvia, including dual floral colors within natural populations—either pale purple or pale yellow. Morphologically, while it shares similarities with members of sect. Glutinaria, S. guidongensis is distinct in its floral morphology, stature, and specific foliar traits. Phylogenetic analysis places S. guidongensis in a unique clade within the East Asian lineage of Salvia, suggesting it may serve as an important evolutionary link. Additionally, we explored the plastome features of S. guidongensis, comparing them with those of closely related species. Discussion The discovery of S. guidongensis not only entriches the taxonomic tapestry of Salvia but also provides critical insights into the biogeography and evolutionary pathways of the genus in East Asia. By integrating morphological and molecular data, we validate the novel status of S. guidongensis and highlight its significance in bridging taxonomic and evolutionary gaps within Sect. Glutinaria of Salvia.